Flipping the classroom in physiotherapy education: experiences, opportunities and challenges - Yngve Røe; Nina B. Ødegaard; Tone Dahl-Michelsen (Universitetsforlaget, 2018)
Abstract In higher education, resistance to shifting educational methods presents a challenge in fulfilling the opportunities offered by new methods. The purpose of the present study is to document the experiences of a flipped classroom intervention in a Norwegian physiotherapy programme, from the perspectives of the students and the teachers. The findings demonstrate that the students' attitudes were mainly positive. In particular, the students evaluated autonomous group work and unlimited access to digital material as positive. The academic outcomes from the final exam were similar to previous years. Interviews with the teachers showed that the learning environment associated with the group work in the flipped classroom was a different and highly appreciated experience. In conclusion, the present study indicates that there is potential in implementing digital approaches in physiotherapy programmes.